DIDACTIC GAMES AS A MEANS OF DEVELOPING STUDENTS' MOTIVATION FOR COGNITIVE ACTIVITY (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article discusses the task of increasing students' interest in mathematics through the use of gaming educational technologies. The expected learning outcomes of using didactic games are presented.